2011
DOI: 10.5210/ojphi.v3i2.3631
|View full text |Cite
|
Sign up to set email alerts
|

Patient-Held Maternal and/or Child Health Records: Meeting the Information Needs of Patients and Healthcare Providers?

Abstract: Though improvements in infant and maternal mortality rates have occurred over time, women and children still die every hour from preventable causes. Various regional, social and economic factors are involved in the ability of women and children to receive adequate care and prevention services. Patient-held maternal and/or child health records have been used for a number of years in many countries to help track health risks, vaccinations and other preventative health measures performed. Though these records are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(37 citation statements)
references
References 91 publications
2
34
0
1
Order By: Relevance
“…A review of research on maternal information seeking behaviors concluded that expectant mothers from developing countries and low-income expectant mothers from developed countries preferred interpersonal information sources. 16 Low health literacy levels were associated with less use of the Internet among low-income expectant mothers in urban Midwestern United States. 17 An Australian study that surveyed expectant mothers of middle-income and higher-income found that for the women who received midwife-led pregnancy care, their midwife was their most useful source of information, whereas for the women who received most of their care from a doctor in an antenatal clinic, the Internet was their most useful source of information.…”
Section: Discussionmentioning
confidence: 99%
“…A review of research on maternal information seeking behaviors concluded that expectant mothers from developing countries and low-income expectant mothers from developed countries preferred interpersonal information sources. 16 Low health literacy levels were associated with less use of the Internet among low-income expectant mothers in urban Midwestern United States. 17 An Australian study that surveyed expectant mothers of middle-income and higher-income found that for the women who received midwife-led pregnancy care, their midwife was their most useful source of information, whereas for the women who received most of their care from a doctor in an antenatal clinic, the Internet was their most useful source of information.…”
Section: Discussionmentioning
confidence: 99%
“…The high record ownership for younger children observed in the provincial data may indicate that younger children had more opportunities to obtain their record if it was provided to their mothers before childbirth, such as in the form of the MCHHB. Providing the MCHHB before birth may have addressed mothers’ need for information about basic infant and child development and care, which is often lacking in developing countries (35). However, further investigation would be needed to determine whether MCHHB distribution increases earlier service access after childbirth.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that patient-held medical records could play an important role in monitoring the continuity of health service use 25 , 26 . Here we investigated a method for using patient-held records – a so-called family planning card – to collect contraceptive data.…”
Section: Introductionmentioning
confidence: 99%